Near-Fatal Self-Harm Among Canadian Adolescents. (August 2022) - Mitchell, Rachel HB; Ani, Cornelius; Cyr, Claude; Irvine, James; Joffe, Ari R; Skinner, Robin; Wong, Sam; Stang, Antonia S; Laffin, Melanie; Korczak, Daphne J
Objective: To evaluate the clinical features of Canadian adolescents admitted to the intensive care unit (ICU) for medically serious self-harm. Methods: 2700 Canadian paediatricians were surveyed monthly over two years (January 2017 to December 2018) through the Canadian Paediatric Surveillance Program to ascertain data from eligible cases. Results: Ninety-three cases (73 female; age 15.2 ± 1.5) met the case definition. Four provinces reported the majority of cases: Quebec (n = 27), Ontario (n = 26), Alberta (n = 21), and British Columbia (n = 8). There were 10 deaths, 9 by hanging. Overdose and hanging were the most frequently reported methods of self-harm (74.2% and 19.4%, respectively). Overdose was more common in females (80.8% females vs. 50% males; χ 2 = 7.8 (1), p = .005), whereas hanging was more common in males (35% males vs. 15.1% females, χ 2 = 3.9 (1), p = .04). More females than males had a past psychiatric diagnosis (79% vs. 58%; χ 2 = 4.1 (1), p = .06), a previous suicide attempt (55.9% vs. 29.4%, χ 2 = 3.8 (1), p = .05), and prior use of mental health service (69.7% vs. 27.8%, χ 2 = 10.4 (1), p = .001). Family conflict was the most commonly identified precipitating factor (43%) of self-harm. Conclusions: Among Canadian adolescents admitted to the ICU with medically serious self-harm, females demonstrate a higher rate of suicide attempts and prior mental health care engagement, whereas males are more likely to die by suicide. These findings are consistent with data from other adolescent samples, as well as data from working-age and older adults. Therefore, a sex-specific approach to suicide prevention is warranted as part of a national suicide prevention strategy; family conflict may be a specific target for suicide prevention interventions among adolescents.